Analisis Kemampuan High Order Thingking Skill Siswa dalam Menyelesaikan Soal Program Linear - Yolandari, Anisa; Avorika, Damar Cinta; Oktarina, Gita; Letron, Letron; Bunda, Monika Sulistia Permata; Al Luthfi, Muhammad Rafif; Kairuddin, Kairuddin (Innovative: Journal Of Social Science Research, 2025)
This research aims to examine high-order thinking skills (HOTS) of students in solving linear programming problems at the high school level. The study employed a descriptive qualitative approach, involving students from XI MIPA 2 at SMA Negeri 9 Bengkulu City. The research focuses on three primary dimensions of HOTS: analysis, evaluation, and creativity in mathematical problem-solving. Research findings reveal significant variations in students' thinking capabilities. Students with high intellectual capacity demonstrated superior abilities in decomposing, assessing, and developing complex mathematical solutions. Conversely, students with medium and low capabilities encountered substantial challenges in interpreting information, constructing mathematical models, and generating accurate solutions.